Toponimi Kampung Sarkanjut Nenggeng dan Cibudug dalam Persfektif Hermaneutik - Hadianto Hadianto (Pascasarjana ISBI Bandung, 2020)
The naming of a village is not only based on geographical location, but also on the psychological character of the village. As in Leuwigoong Subdistrict, the naming of the village is from an oral tradition, namely